Restorative Justice for Settlement of Minor Maltreatment in the Legal Area of the Merangin Police, Jambi Province - Abdul Gani, Ruslan; Wardani, Retno Kusuma (Al-Risalah, 2023)
The aim of this research is to analyze the implementation of restorative justice in resolving minor cases of maltreatment. By emphasizing the utilization of restorative justice, the resolution of these cases occurs outside the courtroom, focusing on restoring the well-being of the victim and facilitating mutual forgiveness between the victim and the perpetrator. The implementation of restorative justice in this context is guided by the Republic of Indonesia National Police Regulation Number 8 of 2021. To conduct this research, empirical juridical methods were employed, and field data collection techniques were utilized, including primary data gathered through interviews with the Head of Bareskrim and the parties involved. Additionally, secondary data in the form of documentation, annual reports, and relevant research journals were collected. The results showed that the settlement of minor crimes in restorative justice had been carried out by the applicable Police Chief Regulations. Second, the obstacles encountered during the settlement process did not hinder investigators from successfully implementing restorative justice within the jurisdiction of the Merangin Police.